Decrypting Google’s Search Engine Bias Case: Anti-Trust Enforcement in the Digital Age - Bhamore, Suyash (Christ University Law Journal, 2019)
For a long time, there has been uncertainty and uneasiness regarding the application of competition law in the digital ecosystem. It is only recently that the evolving Indian competition regime has started facing some of these concerns. In the light of the Competition Commission of India’s (CCI) recent encounter with the search-technology giant Google, the paper provides a much needed analysis of the watershed judgment, considering the likely effects it will have on future competition law jurisprudence. CCI has for the first time, by comprehensively analysing the interplay of antitrust laws and tech market, laid down the basic ground work for subsequent cases. The paper begins with probing into the logic and rationale given by CCI in assessing the relevant market, and Google’s dominant position in such relevant market. Later, the paper examines if the unique features of digital markets have been incorporated, while analyzing Google’s specialized search designs, namely Universal Results, OneBoxes and Commercial Units. Drawing attention to some key concerns like the lack of evidence-based analysis by CCI, the paper concludes by suggesting a suitable remedy and summarizing the key takeaways from the discourse.